Spontaneous expanding internal oblique hematoma induced by vigorous cough in an elderly patient under antiplatelet therapy: Case report and review of literature - Reddy Ravikanth (Wolters Kluwer Medknow Publications, 2019)
Oblique muscle hematomas are an uncommon cause of acute abdominal pain and are more common in elderly individuals, particularly in those under anticoagulant therapy. They are often misdiagnosed from other causes of abdominal pain. We report a case of a cough-induced internal oblique hematoma in an elderly 62-year-old male patient under antiplatelet therapy. He had no history of trauma and presented with acute worsening pain in the left flank. Ultrasonography revealed a hypoechoic mass in the right lateral abdominal wall. Nonenhanced computed tomography of the abdomen showed a 6 cm × 4 cm × 7 cm hematoma in the left internal oblique muscle. The patient was managed conservatively without blood transfusion. Differential diagnosis of an acute-onset flank mass should include oblique muscle hematoma even in the absence of anticoagulant therapy or trauma.